2018
DOI: 10.3389/fnins.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Dorsolateral Prefrontal Cortex in Error Awareness: Single-Pulse TMS Evidence

Abstract: Background: Error awareness is essential to maintain an adaptive and goal-directed behavior and is supposed to rely on the activity of the right dorsolateral prefrontal cortex (DLPFC). However, studies employing electrophysiological methods and functional resonance imaging (fMRI) do not allow to establish a causal relationship between error awareness and implicated brain structures.Objective: The study examined the causal relationship between DLPFC activity and error awareness in order to confirm the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
15
2
Order By: Relevance
“…The selected target areas were the right and left DLPFC. As previously remarked, lateral prefrontal regions have been suggested to be involved in error awareness together with the well-known role of medial frontal cortex (Harty et al, 2014;Masina et al, 2018). Interestingly, a recent study showed a relationship between the left DLPFC and PES (Mansouri et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The selected target areas were the right and left DLPFC. As previously remarked, lateral prefrontal regions have been suggested to be involved in error awareness together with the well-known role of medial frontal cortex (Harty et al, 2014;Masina et al, 2018). Interestingly, a recent study showed a relationship between the left DLPFC and PES (Mansouri et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
“…According to Cieslik et al (2013), the MNI coordinates of the right DLPFC were 30, 43, 23, whereas the MNI coordinates of the left DLPFC were −30, 43, 23. These MNI coordinates were selected because, in a previous study, Masina et al (2018) identified that these coordinates were causally associated with two brain areas involved in error awareness, namely the right and left DLPFC. The position of the Vertex was the Cz site of the International 10-20 system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As is found by previous studies, the right dorsolateral prefrontal cortex (DLPFC) plays a fundamental role in top-down regulatory processes of cognitive control (Botvinick et al, 2001 ; Nunez et al, 2005 ; Vanderhasselt and Raedt, 2009 ; Cieslik et al, 2013 ; Gbadeyan et al, 2016 ; Boschin et al, 2017 ), especially solving the conflicting effects in the Stroop (Vanderhasselt et al, 2007 ; Boschin et al, 2017 ; Masina et al, 2018 ; Seok and Sohn, 2018 ) and Flanker tasks (Gbadeyan et al, 2016 ; Chen et al, 2018 ). While the checking process reflects the conflict cost (Li et al, 2009 ) on performance of relations detection, it is assessed as the difference in response time (RT) between invalid and valid trials.…”
Section: Introductionmentioning
confidence: 99%